A review of metal-organic frameworks/graphitic carbon nitride composites for solar-driven green H2 production, CO2 reduction, and water purification. Issue 3 (June 2022) - Usman, Muhammad; Zeb, Zonish; Ullah, Habib; Suliman, Munzir H.; Humayun, Muhammad; Ullah, Latif; Shah, Syed Niaz Ali; Ahmed, Usama; Saeed, Muhammad
Abstract: The rapid increase in population growth and economic development led to the increase in utilization of fossil fuels energy per capita. Thus, the consumption of these fossil fuel's energy resources poses serious implications for our environment. Photocatalysis plays an essential role in sustainable energy development and environmental remediation. The graphitic carbon nitride (g-C3 N4 ) has been efficiently employed in photocatalysis due to its abundance, low price, high stability, appropriate band gap, and encouraging environmental impacts. As the photocatalytic efficiency of single component g-C3 N4 is still not satisfactory for efficient photocatalysis. Hence, its composites with various functional nanomaterials have been widely prepared and employed for efficient photocatalysis. Among the widely coupled functional nanomaterials, metal-organic frameworks (MOFs) have been widely explored for energy production and controlling environmental pollution due to their large surface area, tunable pore size and window, and tailored functionalities. The significance of MOF/g-C3 N4 composites flourished for green hydrogen (H2 ) production, carbon dioxide (CO2 ) conversion, and environmental pollution control. In this review, we comprehensively highlighted the recent advancements and challenges of g-C3 N4 and MOFs heterojunctions in the field of green H2 production. Besides, we discussed the up-to-date applications of g-C3 N4 -based composites with MOFs for CO2 conversion to useful fuels. Furthermore, the association between MOFs and g-C3 N4 composites and their performance for water purification are also discussed. Finally, we proposed the future potential of MOF/g-C3 N4 composites to be used for the generation of green energy in order to solve environmental issues. We suggest that this review can help to design MOF/g-C3 N4 composite photocatalysts for prospective applications in energy harvesting and controlling environmental pollution. Graphical Abstract: ga1 Highlights: In this review, we highlighted the recent advancements and challenges of MOFs/g-C3 N4 composites. The solar-driven H2 generation, CO2 reduction, and wastewater treatment applications are summarized. Perspectives on the improvement of MOFs/g-C3 N4 composites are proposed.